1998
DOI: 10.3168/jds.s0022-0302(98)75662-0
|View full text |Cite
|
Sign up to set email alerts
|

Ash Content of Detergent Fibers in Feeds, Digesta, and Feces and Its Relevance in Fiber Digestibility Calculations

Abstract: The influence of insoluble ash in diet, digesta, and fecal samples was evaluated. Ash-free values of neutral detergent fiber (NDF) and acid detergent fiber (ADF) for feed, digesta, and fecal samples were compared with uncorrected values of NDF and ADF in two digestibility experiments. Six feed samples were selected at random along with four duodenal and two fecal samples; the latter two were a part of two digestion studies. The silica composition of feed samples was low with the exception of oat hay and rice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…This was unexpected particularly because fecal ADF output was likely overestimated, being not corrected for ash. Crocker et al (1998) reported that the total-tract digestibilities of ash-free NDF were greater than that of NDF (inclusive of ash) in 2 experiments using lactating dairy cows, with same responses observed for digestibilities of ash-free ADF versus ADF (inclusive of ash). Thus, if the fecal output of ADF from the current study would have been corrected for ash, the difference between ADF and aNDFom digestibility could be even larger than 13 percentage units.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…This was unexpected particularly because fecal ADF output was likely overestimated, being not corrected for ash. Crocker et al (1998) reported that the total-tract digestibilities of ash-free NDF were greater than that of NDF (inclusive of ash) in 2 experiments using lactating dairy cows, with same responses observed for digestibilities of ash-free ADF versus ADF (inclusive of ash). Thus, if the fecal output of ADF from the current study would have been corrected for ash, the difference between ADF and aNDFom digestibility could be even larger than 13 percentage units.…”
mentioning
confidence: 62%
“…Thus, it appears that differences were exacerbated when aNDFom rather than NDF was used despite the reasons behind these discrepancies remain to be elucidated. Crocker et al (1998) concluded that the use of ash-free NDF and ADF resulted in more realistic and accurate digestibility estimates of fiber in the rumen and total tract. They also concluded that sample contamination by silica and other ash components may influence NDF and ADF concentrations if the fiber residues are not ashed before calculations of NDF and ADF digestibility (Crocker et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated cellulose content by subtracting the lignin content from the acid‐detergent fibre content (Vansoest et al., 1991). This portion of acid‐detergent fibre typically also includes a minor mineral component, made up primarily of silica (Crocker et al., 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The negative NDF digestion postruminally is possible; however, it is probably an artifact of the assay. Crocker et al (1998) minal NDF digestibility was significantly lower (P < 0.007), and apparent postruminal NDF digestibility was significantly greater (P < 0.0004) for cows fed diets containing hybrid Quanta compared to cows fed diets containing hybrid 3845 in experiment 2 (Table 6).…”
Section: Intake and Digestionmentioning
confidence: 97%